European Landed Elites in the Nineteenth Century - Spring, David (Johns Hopkins University Press, 2020)
Originally published in 1977. Professor David Spring presents comparative histories of European landed elites in the nineteenth century, covering English, Prussian, Russian, Spanish, and French landed elites. European Landed Elites in the Nineteenth Century underscores the particularities of each case and underscores the differences between cases.